Global historic pandemics caused by the FAM-1 genotype of Phytophthora infestans on six continents - Amanda C. Saville (Nature Portfolio, 2021)
Abstract The FAM-1 genotype of Phytophthora infestans caused late blight in the 1840s in the US and Europe and was responsible for the Irish famine. We sampled 140 herbarium specimens collected between 1845 and 1991 from six continents and used 12-plex microsatellite genotyping (SSR) to identify FAM-1 and the mtDNA lineage (Herb-1/Ia) present in historic samples. FAM-1 was detected in approximately 73% of the historic specimens and was found on six continents. The US-1 genotype was found later than FAM-1 on all continents except Australia/Oceania and in only 27% of the samples. FAM-1 was the first genotype detected in almost all the former British colonies from which samples were available. The data from historic outbreak samples suggest the FAM-1 genotype was widespread, diverse, and spread to Asia and Africa from European sources. The famine lineage spread to six continents over 144 years, remained widespread and likely spread during global colonization from Europe. In contrast, modern lineages of P. infestans are rapidly displaced and sexual recombination occurs in some regions.